2014
DOI: 10.1097/nne.0000000000000038
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Nursing Student Experiences With Faculty Bullies

Abstract: Incivility literature has focused primarily on student-to-faculty incivility, whereas less focus has been placed on faculty-to-student bullying. This study examined the lived experiences of undergraduate nursing students with faculty bullying. Using descriptive phenomenology, this study explored these lived experiences. Themes emerged including the emotional experience of bullying, the giving and gaining of mutual respect, the value of resilience and persistence, and that perception is reality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 17 publications
2
36
0
Order By: Relevance
“…Although the participants’ uncivil encounters with faculty differed, feeling emotionally traumatized, humiliated and belittled were common among all the shared experiences. This finding is congruent with what previous research discovered about the psychological distress experienced by students exposed to the uncivil faculty behaviour (Altmiller ; Holtz et al ; Mott ). Feelings of anxiety, fear and nervousness experienced by participants were also the most commonly shared emotions by students (Clark ; Vuolo ).…”
Section: Discussionsupporting
confidence: 92%
“…Although the participants’ uncivil encounters with faculty differed, feeling emotionally traumatized, humiliated and belittled were common among all the shared experiences. This finding is congruent with what previous research discovered about the psychological distress experienced by students exposed to the uncivil faculty behaviour (Altmiller ; Holtz et al ; Mott ). Feelings of anxiety, fear and nervousness experienced by participants were also the most commonly shared emotions by students (Clark ; Vuolo ).…”
Section: Discussionsupporting
confidence: 92%
“…First, the study focused on exploring bullying behaviors experienced by nursing students in the clinical setting. While it is possible that students may experience bullying behaviors from other potential perpetrators (e.g., classmates, academic faculty (Mott, 2014; Seibel, 2014)] and in other settings (e.g., classroom, on-campus), or may engage in bullying behaviors themselves (Kolanko et al, 2006), participants were not asked to explore these aspects. Therefore, results reported may only represent one aspect of nursing students’ experiences with bullying behaviors their academic program.…”
Section: Discussionmentioning
confidence: 99%
“…Classmates were identified as the most frequent perpetrators of verbal abuse followed by faculty. [30][31][32][33] These studies provide significant evidence to support nursing students' vulnerability to incidences of bullying in multiple settings during their undergraduate education.…”
Section: Prevalence Ratesmentioning
confidence: 91%
“…Further studies identified a multitude of adverse physical and psychological symptoms in response to bullying including headaches, gastrointestinal problems, sleep disturbance, anxiety, tearfulness, depression, suicidal ideation, shame, loss of confidence and self-esteem, and inability to effectively learn. 6,24,[31][32][33][34] In response to bullying, 1 study noted the majority of nursing students reported doing nothing because of an overriding sense of powerlessness to change their situation and a lack of confidence in their ability to effectively intervene. 24 This silence suggests an underreporting of bullying experienced and a potential that bullying will continue within the clinical and professional environment as nursing students transition to full practice.…”
Section: Impactmentioning
confidence: 96%